Gold-catalyzed glycosidations: synthesis of 1,6-anhydro saccharides - Thadke, Shivaji A.; Hotha, Srinivas (Tetrahedron Letters, 2010)
Various 1,6-anhydro sugars are synthesized utilizing salient features of gold-catalyzed glycosidations. All the reactions occurred under mild conditions in the presence of 7 mol % of AuBr(3) enabling easy synthesis of 1,6-anhydro sugars from corresponding 6-hydroxy propargyl/methyl monosaccharides, disaccharides, and trisaccharides in good yields. (C) 2010 Elsevier Ltd. All rights reserved.